IMPLEMENTASI KOMPENSASI DAN BENEFIT: TINJAUAN MANAJEMEN SDI BERBASIS SYARI’AH - Khasbulloh, Muhammad Nabil (Universitas Negeri Surabaya, 2018)
Recently, the development of companies increasing rapidly and competitively, the companies has to compete each other in order to gain and preserve their qualified -human resources. Compentation and benefit are the one of the usual managing strategies to fullfil it and it is interesting topic to notes and to challenges for the managers, is how the system can maintain a sense of equity (internal evenly) with the amount of labor (external competitiveness). In order for the balance occurs then the managers do maintenance of the system and the value of these values. The Qur'an and Al-Hadith have explained and benefited the rewards that one receives upon his work in the form of covenant in the world and in the Hereafter. In its implementation of benefits from the perspective of syariah, human resource management should pay attention to the benefits aspect. Therefore, to be able to implement these aspects of shari'ah, payroll management is done by using